ChemInform Abstract: The Multiple Facets of Iodine(III) Compounds in an Unprecedented Catalytic Auto‐Amination for Chiral Amine Synthesis. Issue 43 (7th October 2016) - Buendia, Julien; Grelier, Gwendal; Darses, Benjamin; Jarvis, Amanda G.; Taran, Frederic; Dauban, Philippe
Abstract: Diacetoxyiodoarene (III) is used both as an oxidant and a substrate for the C(sp 3 )—H amination reaction leading to chiral iodide (V).